Transient analysis of the radiative heating of rotating PVC pipes in a oven for end-forming process. (25th January 2018) - Lucchi, M.; Lorenzini, M.
Highlights: The radiative heating stage in the end-forming process of PVC pipes is studied. A mathematical model for the local view factors profile was introduced. Simulations completely justified the use of rotational devices in this process. Temperature non-uniformity and angular velocities showed a non-linear relationship. The model can be used to determine the suitable angular velocities for the process. Abstract: In polymer industry several applications are aimed at obtaining products by deforming preforms or sheets after a heating process which, if not carried out properly, may lead to unacceptable defects in the final product. A common example of such an application is the end-forming process of polyvinyl chloride (PVC) tubes, in order to allow piping connections. One end of the tube undergoes a deformation process preceded by a heating phase, which is conducted in a oven equipped with infrared lamps. The pipe rotates with a given angular velocity, in order to ensure uniform heating. Hence, the pipe angular velocity represents a fundamental parameter for the proper success of end-forming process. In this work, the transient analysis of the radiative heat exchange between rotating PVC pipes and infrared lamps of a oven for end-forming process has been carried out by means of a finite element model, in order to investigate the influence of cylinder angular velocity on the temperature distribution in the tube. Local view factors were calculated as a function of geometry and oven configuration and were expressed as a function of angular velocity, allowing pipe rotation to be simulated as a time-dependent boundary condition, instead of using a moving mesh. Simulations were carried out for tubes of different geometries and for different values of angular velocity and results were compared with the case of a uniformly irradiated tube. The model realized represents a tool to characterize the end-forming process for different polymeric materials and different oven configurations.